(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
The Netherlands-Indies/Indonesian pavilions for international expositions are interesting and important to be studied because, as they were limited in number, they can tell the story of Indonesia’s point of view, situation, progress, and vision over time. Moreover, considering the huge diversity of ethnicities and cultures, the pavilions can be taken as a lesson on how Indonesia sees diversity and represents it in a ‘small’ building. This study aims to comprehend the meaning of the pavilions’ architecture and how they were constructed by discussing collected images and texts about those pavilions. The research objects are pavilions from three exhibitions during the Netherlands-Indies period and four from the Indonesian period. This qualitative comparative study uses content analysis from literary and visual sources in their context. It was found that the architectural image of the pavilions played an important role in responding to the expo theme, displaying diversity and identity, and giving a narration about Indonesia.